(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: The study aimed to describe the results of interventional gastrointestinal endoscopy in patients with gastrointestinal diseases at Song Lo district Medical Center and Vinh Phuc provincial General Hospital period 2023-2024. Research methods: A total of 51 patients underwent interventional gastrointestinal endoscopy. Data collection involved structured questionnaire interviews with research subjects and a review of hospital medical records. Data were entered into Epiinfo software (V.3.1) and analyzed using SPSS software (V.20.0). Results: The implementation of interventional gastrointestinal endoscopy for patients with gastrointestinal diseases at Song Lo district Medical Center and Vinh Phuc provincial General Hospital period 2023-2024 was highly successful (100%). The intestinal parenchyma recovery time within 60 minutes was 100%. There were no complications, adverse events, referrals to higher-level hospitals, or deaths. Conclusion: Song Lo district Medical Center should promptly complete the transfer of routine interventional gastrointestinal endoscopy techniques to better serve patients, prevent overloading at higher-level hospitals, and reduce costs for patients.